2023
DOI: 10.1039/d2va00325b
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical formation of water-soluble oxyPAHs, naphthenic acids, and other hydrocarbon oxidation products from Cook Inlet, Alaska crude oil and diesel in simulated seawater spills

Abstract: Hydrocarbon oxidation products (HOPs) formed from crude oil and diesel were formed from laboratory simulated spills at four different periods (1, 4, 7, and 10 days) with environmental conditions that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 119 publications
0
7
0
Order By: Relevance
“…The increases in viscosity, density, and water-soluble content, and decreases in IFT for irradiated oil may be explained by the production of oxygenated species (Figure ) and/or photochemically driven changes in molecular weight. Photo-oxygenated oil products are molecularly diverse, representing a continuum from relatively nonpolar oil-soluble compounds to more highly oxygenated and polar material that is interfacially active or even water-soluble (Figures and ). ,, Light-driven increases in oil viscosity and density may reflect the production of higher molecular weight (photo-polymerized) and polar oxygenated components with strong intermolecular forces (Figure A,D). ,,,, Simultaneously, the decrease in IFT and increase in dissolution for photochemically weathered oil may reflect the presence of lower molecular-weight species that are more polar than the bulk irradiated oil (Figure B,C). ,, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increases in viscosity, density, and water-soluble content, and decreases in IFT for irradiated oil may be explained by the production of oxygenated species (Figure ) and/or photochemically driven changes in molecular weight. Photo-oxygenated oil products are molecularly diverse, representing a continuum from relatively nonpolar oil-soluble compounds to more highly oxygenated and polar material that is interfacially active or even water-soluble (Figures and ). ,, Light-driven increases in oil viscosity and density may reflect the production of higher molecular weight (photo-polymerized) and polar oxygenated components with strong intermolecular forces (Figure A,D). ,,,, Simultaneously, the decrease in IFT and increase in dissolution for photochemically weathered oil may reflect the presence of lower molecular-weight species that are more polar than the bulk irradiated oil (Figure B,C). ,, …”
Section: Discussionmentioning
confidence: 99%
“… , Moreover, cold temperatures are unlikely to substantially suppress oil photo-reactivity: Previous work on diverse crude oils showed that photochemical oxidation of oil changed by 30% at most across a temperature change of 10 °C (Figure S3). Further, high-latitude experiments conducted under a range of temperature and irradiance conditions, both with and without the presence of sea ice, have shown photochemical degradation of specific compound classes (e.g., steranes, polycyclic aromatic compounds) and oxygenation of hydrocarbons. However, the scientific community does not yet know how the properties and partitioning behavior of photochemically weathered oil would change in a cold environment.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments selected for pathway inhibition included 10 mg L –1 SRFA with the addition of either 17.5 mM isopropanol (IPA), 5 mM furfuryl alcohol (FFA), or 1 mM trimethylphenol (TMP) to selectively quench • OH, 1 O 2 , and 3 CDOM*, respectively. All microcosms were incubated under simulated solar conditions typical of Southcentral Alaska summers (250 W m –2 ), using a SunTest XLS+ with a suncool attachment for air temperature regulation (Atlas Materials, Mount Prospect, IL). Experiments were conducted first at 20 °C in quartz test tubes and then repeated at 4 and 12 °C in water cooled jacketed beakers covered with a saran wrap film.…”
Section: Methodsmentioning
confidence: 99%
“…Calculations for illumination-position-corrected first-order rate constants ( j ), half-lives ( t 1/2 ), and apparent quantum yields (ϕ) for the photochemical degradation of 6PPDQ by simulated sunlight were previously described . Briefly, j (h –1 ) were calculated from eq ln ( C t / C 0 ) F normalP = j t where C 0 and C t are the concentration (ppb) of 6PPDQ at time t (h), respectively, and F P is the illumination correction factor calculated via 2NB actinometry.…”
Section: Methodsmentioning
confidence: 99%
“…Harsha et al 72 utilized complementary non-targeted and targeted techniques, including high-resolution mass spectrometry, fluorescence excitation–emission matrix spectroscopy, and liquid chromatography-triple quadrupole mass spectrometry, to monitor how the composition of hydrocarbon oxidation byproducts (HOPs) from Cook Inlet, Alaska crude oil and diesel changed over time due to variations in fuel types and exposure durations. The results showed that the HOPs from crude oil exhibited a higher aromatic nature and those from diesel were more aliphatic.…”
Section: Oil Photochemistrymentioning
confidence: 99%